Elucidating the Interactions Between Heparin/Heparan Sulfate and SARS-CoV-2-Related Proteins—An Important Strategy for Developing Novel Therapeutics for the COVID-19 Pandemic - Yu, Mingjia; Zhang, Tianji; Zhang, Wei; Sun, Qianyun; Li, Hongmei; Li, Jin-ping (Frontiers in Molecular Biosciences, 2021)
Owing to the high mortality and spread rates, the infectious disease caused by coronavirus has become a major threat to public health and social economy. Since there is currently no effective therapeutic or preventive vaccine available, it is of urgent need investigating new strategies for the treatment of coronavirus infection. Binding of a viral protein onto cell-surface heparan sulfate (HS) is generally the first step in a cascade of interaction that is required for viral entry and the initiation of infection. Meanwhile, interactions of selectins and cytokines (eg. IL-6 and TNF-α) with HS expressed on endothelial cells are crucial in controlling the recruitment of immune cells during inflammation, which possibly lead to a severe cytokine storm. Thus, structurally defined heparin/HS and their mimetics might serve as potential drugs by competing with cell-surface HS for the prevention of viral adhesion and acute inflammatory reaction. In this review, we will summarize the latest advances in HS-protein interactions, especially proteins relevant to the process of coronavirus infection and subsequent inflammation. Experimental and computational techniques involved will be emphasized.